Patient-specific organotypic blood vessels as an in vitro model for anti-angiogenic drug response testing in renal cell carcinomaResearch in context - José A. Jiménez-Torres; María Virumbrales-Muñoz; Kyung E. Sung; Moon Hee Lee; E. Jason Abel; David J. Beebe (EBioMedicine, 2019)
Background: Anti-angiogenic treatment failure is often attributed to drug resistance, unsuccessful drug delivery, and tumor heterogeneity. Recent studies have speculated that anti-angiogenic treatments may fail due to characteristics inherent to tumor-associated blood vessels. Tumor-associated blood vessels are phenotypically different from their normal counterparts, having defective or permeable endothelial monolayers, abnormal sprouts, and abnormal vessel hierarchy. Therefore, to predict the efficacy of anti-angiogenic therapies in an individual patient, in vitro models that mirror individual patient's tumor vascular biology and response to anti-angiogenic treatment are needed. Methods: We used a microfluidic in vitro organotypic model to create patient-specific biomimetic blood vessels from primary patient-specific tumor endothelial cells (TEnCs) and normal endothelial cells (NEnC). We assessed number of sprouts and vessel organization via microscopy imaging and image analysis. We characterized NEnC and TEnC vessel secretions via multiplex bead-based ELISA. Findings: Using this model, we found that TEnC vessels exhibited more angiogenic sprouts than NEnC vessels. We also found a more disorganized and gap-filled endothelial monolayer. NEnCs and TEnC vessels exhibited heterogeneous functional drug responses across the five patients screened, as described in the clinic. Interpretation: Our model recapitulated hallmarks of TEnCs and NEnCs found in vivo and captured the functional and structural differences between TEnC and NEnC vessels. This model enables a platform for therapeutic drug screening and assessing patient-specific responses with great potential to inform personalized medicine approaches. Funding: NIH grants R01 EB010039, R33 CA225281, R01CA186134 University of Wisconsin Carbone Cancer Center (CA014520), and University of Wisconsin Hematology training grant T32 HL07899. Keywords: Organotypic, Lumen, Model, Anti-angiogenic, Renal, Carcinoma